PERAN PUPUK N DAN P TERHADAP SERAPAN N, EFISIENSI N DAN HASIL TANAMAN JAHE DI BAWAH TEGAKAN TANAMAN KARET - Bambang Gonggo Murcitro; Hasanudin Hasanudin; Yuni indriani (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2006)
Area under rubber tree stands has an economic potential for production of ginger if proper fertilizer application is implemented. Purpose of this study was to determine the effects of N and P fertilizers application on N uptake, N efficiency and yield of ginger grown under rubber tree stands. The experiment was laid in RCB design with a factorial arrangement of the treatments, consisted of four levels of N fertilizer (0, 3.375, 6.75, and 10.125 g plant-1) and three levels of P fertilizer (0, 9, and 18 g plant-1). There were three replications and 18 plant on each experimental unit. Results indicated that there were significant interaction effects between N and P fertilizers on N uptake and N efficiency. The expected maximum N efficiency of ginger plant was 14.01% as N fertilizer applied alone at 12.56 g plant-1. Similarly, the highest N uptake (1.170 g plant-1) was observed on N application at 13.755 g plant-1 without P. Weight of ginger rhizome was predicted to increase 0.2203 g plant-1 on 1 % increment of N uptake efficiency.